Teacher's Strategies In Motivating Students For Learning Vocabulary At MI Al Islam Jamsaren Surakarta - Asiyah, Nur (2012)
The objectives of the study are as follows: 1) to describe teacher's strategies in motivating the first-year students for leaning vocabulary, 2) to describe the implementation of teacher's strategies in motivating the first-year students for learning vocabulary, 3) to describe the problems on the implementation of the teacher's strategies in motivating the first-year students for learning vocabulary, 4) to describe problems solving of the implementation of the teacher's strategies in motivating the first-year students for leaning vocabulary at MI Al Islam Jamsaren Surakarta. It is a descriptive qualitative research conducted at the first year students of MI Al Islam Jamsaren Surakarta. The techniques for collecting data are conducting observation, interviewing, and analyzing document. The data are analyzed through data reduction, data display, and conclusion and verification. The results of the study show that: 1) Teacher's strategies to motivate the students in learning English are six strategies in teaching English, namely vocabulary and language development, guided instruction, metacognition and authentic assessment, explicit instruction, meaning-based context and universal themes, and modeling, graphic organizers, and visual aid. 2) The implementation of those strategies, namely using picture, replicated thing, attach and coloring, vocabulary card, singing a song, game and making small group. 3) The problems faced in the classroom during teaching learning process are: first, students were so active. They didn't want to be quite and stay on their chairs. Second, time consuming in preparing material and learning media. Third, teacher's voice is too low. The voice can't achieve around the class. 4) The solutions found by the teacher in solving the problem are by making a game and giving reward, the teacher prepares materials for the next meeting after the class has been over, and the teacher divides the students into small groups and asks each group in turn to get closer to the teacher when the teacher explains the material.